Unveiling hidden leprosy in underserved populations of the Amazonas state through active case-finding—the Amazon Skin Health Program (2023) - Grana, Aline; Chirano, Carlos Alberto; Talhari, Sinesio; de Sousa, Débora Raysa Teixeira; de Souza, Lucia Tatiana Filgueiras; Leturiondo, André Luiz; de Oliveira Ferreira, Cynthia; da Silva Cruz, Rossilene Conceição; Pedrosa, Valderiza Lourenço; Miot, Helio Amante [UNESP]; Talhari, Carolina (Wiley, 2025)
Background: Active case-finding is an effective strategy for combating leprosy, especially in early multibacillary cases in endemic regions. This early approach includes systematic actions such as epidemiological investigations, community surveys, and awareness campaigns to identify leprosy cases. This study reports new leprosy cases diagnosed through an active case-finding initiative conducted in 12 underserved populations from Amazonas in 2023. Methods: This is a cross-sectional descriptive study focused on patients diagnosed with leprosy and other dermatological diseases during the multi-professional Amazon Skin Health Program. Data collected for all suspected cases of leprosy encompassed epidemiological information, clinical details, slit skin smear test, histopathological examination, and polymerase chain reaction (PCR) test. Results: Among 13,023 individuals examined, 69 (0.53%) new cases of leprosy were detected: 46.38% were characterized as paucibacillary and 53.62% as multibacillary. Regarding their age and neurologic involvement, 10.1% were detected in children under 15 years, and 20.9% had grade II disability. This effort accounted for an increase of 21.8% in the year-based diagnoses of leprosy in the state of Amazonas. Conclusions: Active case-finding can unveil hidden cases of leprosy in endemic areas, contributing to early detection to prevent neurological impairment and limit disease transmission. Additionally, the results advocate for targeted public health interventions, including the involvement of dermatologists in the diagnostic process and enhanced training for health professionals in differentiating leprosy from other cutaneous diseases.
Keywords: active case-finding; Amazon; Amazon Skin Health Program; leprosy; prevalence; underserved population